Interactive theorem proving : 9th International Conference, ITP 2018, held as part of the Federated Logic Conference, FloC 2018, Oxford, UK, July 9-12, 2018, Proceedings /: 9th International Conference, ITP 2018, held as part of the Federated Logic Conference, FloC 2018, Oxford, UK, July 9-12, 2018, Proceedings. (2018) - Unknown
No abstract available